Lepromatous Lymphadenitis: A Rare Manifestation of Leprosy Diagnosed by Fine Needle Aspiration Cytology - Chitkara, Falguni; Pannu, Diljot; Saha, Debkanya; Makhija , Amay; Kour, Irbinder; Dhawan , Vishesh; Kediya, Ayushi (Annals of Pathology and Laboratory Medicine, 2025)
Introduction: Leprosy is a widespread infectious and contagious disease with a prevalence rate of 0.4 per 10,000 population in India. It is a chronic infectious disease caused by Mycobacterium leprae and mainly affects the skin, the peripheral nerves, the mucosa of the upper respiratory tract, and the eyes. Lymph node involvement is rare. Case Description: A 24-year-old male presented with right lower limb numbness for one year and a non-healing knee ulcer for one month, along with recurrent ulcers. sensory loss, and erythematous macules. Nerve conduction studies showed that the bilateral ulnar and sural nerves were non-excitable, and the median nerves had reduced amplitude. FNAC of a right inguinal lymph node revealed foamy macrophages and ill-defined granulomas; Modified Ziehl-Neelsen stain demonstrated numerous acid-fast bacilli, indicating lepromatous lymphadenitis. A punch biopsy from the knee ulcer showed epithelioid granulomas, foamy macrophages, and a Grenz zone with positive AFB staining. A diagnosis of Borderline Lepromatous (BL) leprosy was confirmed. The patient was started on multidrug therapy and showed clinical improvement. Conclusion: When Leprosy presents as lymphadenopathy, FNAC can be a very useful tool for the diagnosis of Lymphadenopathy due to Leprosy and excludes other possibilities of Lymphadenitis. It is also a simpler, quicker, and less invasive technique for diagnosing such rare lesions.